Amination of Aryl Halides Mediated by Electrogenerated Nickel from Sacrificial Anode. Issue 17 (5th May 2021) - Daili, Farah; Sengmany, Stéphane; Léonel, Eric
Abstract: Electrochemical C(sp 2 )−N couplings mediated by nickel salts generated from the sacrificial anode has been described for the first time. In this approach, the sacrificial nickel anode is employed as the sole source of nickel and the process, operationally simple to set up, enables the preparation of functionalized arylamine derivatives with moderate to good yields, under mild reaction conditions and without additional ligand. A cooperative process between the two electrodes is involved in the proposed mechanism. Abstract : C(sp 2 )−N bond formation only mediated by nickel salts electrogenerated from the sacrificial anode has been investigated for the first time to prepare functionalized arylamine derivatives. The cross‐couplings are performed under constant current electrolysis, in an undivided cell, and without additional ligand at room temperature.